Seasonal Variation of VS at Shallow Depth and Nonlinear Behavior of Soil Based on the ARGONET Vertical Array Data - Roumelioti, Zafeiria; Hollender, Fabrice (Technical Annals, 2024)
Ground acceleration time histories from earthquakes recorded by the ARGONET vertical array in Cephalonia, Greece, in the period from July 2016 to April 2022, are analyzed seeking evidence for nonlinear behavior of the shallow soil layers. Shear waves velocity, VS, between the shallowest sensor pair of the vertical array, i.e., within the top 5.6 m of the soil column, is derived for each earthquake record using the method of interferometry by deconvolution. The temporal variation of VS values is compared with indicators related to soil moisture and this leads to the identification of a clear difference in the level of the measured values between periods of intense rainfall and the dry summer months. Lower velocities, even lower than the level of VS during rainy periods (7-13% of the annual average), are obtained based on the strongest records of the analyzed sample. These low velocities are considered as indicators of nonlinear soil behavior, the threshold onset of which is difficult to determine without prior correction for the seasonal variation. The applied method can provide a detailed description of VS changes even during a single earthquake. Examples are provided on how nonlinear soil behavior may be manifested by a sudden VS value drop at the arrival of the strongest seismic phases.